Perlindungan Kepada Warga Negara Melalui PTUN terhadap Penyalahgunaan Wewenang oleh Pejabat Publik (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
That every decision issued and/or action taken by state administration officials must be based on statutory regulations and General Principles of Good Government (AAUPB). In accordance with Article 9 paragraph (1) of Law no. 30 of 2014 concerning Government Administration, but in practice there are still many government officials who abuse their authority, therefore the existence of PTUN is a tool of control over government actions as well as a medium for the public to seek justice for government actions. Where the Ptun has the authority to resolve TUN disputes, as well as provide legal protection to the community for legal actions taken by the government through the PTUN. This research uses normative research using a conceptual and statutory approach. The legal materials used are: primary legal materials in the form of statutory regulations, secondary legal materials in the form of books, journals, articles and other legal doctrines. The legal material collection technique uses descriptive analysis. It can be concluded that the role of Ptun is in providing legal protection to citizens against detrimental administrative decisions, namely through supervision, giving administrative sanctions to government officials who do not implement court decisions, up to the execution of court decisions in the form of revoking government decisions.